Mapping Global Research Trends in Social Entrepreneurship and Sustainable Development: A Bibliometric Review for Nonformal Education and Community Empowerment - Ummaya Santi, Fitta; Sujarwo, Sujarwo; Rashid, Salman (Journal of Nonformal Education, 2026)
Background - Social entrepreneurship research has experienced rapid growth alongside increasing attention to sustainable development. However, systematic mapping, particularly examining the interrelationships between the two, remains limited, making it difficult to identify development directions and research gaps.Research Urgency - Research on social entrepreneurship and sustainable development is growing rapidly and producing influential work, but it remains dominated by fragmented conceptual approaches. The lack of longitudinal bibliometric mapping has left gaps in understanding the structure of knowledge, the dynamics of themes, and patterns of research collaboration.Research Objectives - This study aims to map publication growth, collaboration patterns, intellectual structure, and thematic evolution of research on social entrepreneurship and sustainable development during 2015–2025. Research Methods - A bibliometric analysis was conducted using 268 English-language journal articles indexed in Scopus. Data were collected on 14 January 2026 using the search string: TITLE-ABS-KEY ("social entrepreneurship" AND "sustainable development"), limited to journal articles (2015–2025). Bibliometric analysis was performed using Biblioshiny and VOSviewer to examine publication trends, collaboration networks, keyword co-occurrence, and thematic development. Research Findings - The findings indicate a significant annual growth rate of 23.37%, reflecting rapid expansion of the field. The dataset involved 752 authors across 163 journals, with an international collaboration rate of 27.24%. Sustainable development emerged as the most central concept in the keyword network, while social entrepreneurship functioned as an operational mechanism within the broader sustainability framework. SDGs, governance, and social innovation were identified as developing themes, indicating conceptual fragmentation.Research Conclusion - This study confirms that social entrepreneurship has become an important instrument of sustainable development, but strengthening conceptual and empirical integration, especially related to SDGs and social innovation, is still needed.Research Novelty - The novelty of the research lies in the ten-year longitudinal bibliometric mapping that reveals publication dynamics as well as strategic thematic gaps as a basis for formulating a future research agenda.